Clonal Hematopoiesis–Associated Gene Mutations in a Clinical Cohort of 448 Patients With Ovarian Cancer. (28th December 2021) - Weber-Lassalle, Konstantin; Ernst, Corinna; Reuss, Alexander; Möllenhoff, Kathrin; Baumann, Klaus; Jackisch, Christian; Hauke, Jan; Dietrich, Dimo; Borde, Julika; Park-Simon, Tjoung-Won; Hanker, Lars; Prieske, Katharina; et al.
Abstract: Background: Cancer patients are at risk of secondary therapy–related myeloid neoplasms (t-MNs). Acquired blood-specific mutations in clonal hematopoiesis (CH)–associated genes are t-MN risk factors, and their occurrence associated with cancer therapy and age. Patients with ovarian cancer (OC) showed a particularly high prevalence of CH–associated gene mutations, which may additionally be explained by the high proportion of a hereditary disease cause in this cancer entity. Methods: We performed a retrospective analysis of 448 OC patients enrolled in the AGO-TR1 study; 249 were enrolled at primary diagnosis and 199 at platinum-sensitive recurrence. Analyses included the most frequently altered CH–associated genes ( ASXL1, DNMT3A, GNAS, JAK2, PPM1D, SF3B1, SH2B3, SRSF2, TET2, TP53 ). Results were analyzed according to the BRCA1/2 germline (g BRCA1/2 ) mutation status. All statistical tests were 2-sided. Results: Advanced age at blood draw and a high number of prior platinum-based chemotherapy lines were risk factors to acquire CH–associated gene mutations, with gene-specific effects observed. Binomial logistic regression suggested increased probabilities for g BRCA1/2 mutation carriers to acquire CH-associated PPM1D and TP53 gene mutations ( PPM1D : odds ratio = 4.30, 95% confidence interval = 1.48 to 12.46, P  =   .007; TP53 : odds ratio = 6.20, 95% confidence interval = 0.98 to 53.9, P  =   .06). This observation was due to a statistically significantly increased number of platinum-based chemotherapy lines in g BRCA1/2 mutation carriers vs noncarriers ( PPM1D : mean [SD] = 2.04 [1.27] vs 1.04 [0.99], P  <   .001; TP53 : mean [SD] = 2.83 [1.33] vs 1.07 [1.01], P  <   .001). No interaction between platinum-based chemotherapy and g BRCA1/2 mutation status with the occurrence of CH–associated gene mutations was observed. Conclusions: A positive g BRCA1/2 mutation status is not a risk factor to acquire CH–associated gene mutations. OC patients may benefit from monitoring CH–associated gene mutations, especially following carboplatin exposure. Future clinical studies are required to assess whether treatment regimen should be adapted according to individual t-MN risks.